Accelerated C♯ 2008 - Nash, Trey (Expert's voice in .NET., 2007)
In this rapid tutorial and permanent reference, Nash teaches both core C♯ language concepts and how to wisely employ C♯ idioms and object-oriented design patterns to exploit the power of C♯ and the CLR.